A methodological remark on in vivo models of experimental subarachnoid hemorrhage [İn vivo deneysel subaraknoid kanama modelleri hakki{dotless}nda metodolojik bir hati{dotless}rlatma] - (:unkn) unknown (My University, 2013)
[No abstract available]
Keywords: Arterial blood; Cerebral vasospasm; Experimental models; Subarachnoid hemorrhage